Identifying Metabolomic Profiles of Insulinemic Dietary Patterns (OR31-03-19). (13th June 2019) - Tabung, Fred; Balasubramanian, Raji; Clinton, Steven; Liang, Liming; Clish, Clary; Giovannucci, Edward; Rexrode, Kathryn
Abstract: Objectives: The empirical dietary index for hyperinsulinemia (EDIH) is a food-based score derived from correlations with plasma c-peptide. Our aim is to use the EDIH to discover metabolites associated with insulinemic dietary patterns. Methods: This baseline cross-sectional study evaluated associations between continuous EDIH scores from food frequency questionnaires and 448 log-transformed plasma metabolites as outcomes in multivariable linear regression analyses. Metabolites were measured with liquid chromatography tandem mass spectroscopy. Metabolite discovery was conducted among 1109 Women's Health Initiative (WHI) Hormone Therapy trial participants and results replicated in an independent dataset of 810 WHI Observational Study participants. In both discovery and replication datasets statistical significance was based on false-discovery rate adjusted P  < 0.05. Secondary analyses were conducted in body mass index (BMI: <25, >=25 kg/m 2 ) categories. Results: After adjustment for energy intake, BMI, physical activity, and other confounding variables, 26 metabolites were significantly associated with EDIH in the discovery dataset, and included: trigonelline, C14:0 CE, C16:1 CE, C18:1 CE, C18:3 CE, C20:3 CE. C20:5 CE, C36:1 PS plasmalogen and eicosapentaenoate were associated with lower dietary insulinemic potential, whereas C36:3 DAG, C51:3 TAG, C52:3 TAG, C52:4 TAG, C54:2 TAG, C54:3 TAG, C54:4 TAG, C54:6 TAG, C36:4 DAG-A, cystathionine, isoleucine, N4-acetylcytidine, C10:2 carnitine, cAMP, C18:2 SM, C4-OH carnitine, and myristoleic acid were associated with higher dietary insulinemic potential. 25 out of the 26 metabolites replicated in the validation dataset except myristoleic acid. In secondary analyses within BMI strata, Associations differed by BMI category: 12 metabolites were significant among normal weight women whereas 64 metabolites were associated with EDIH among overweight/obese women. Conclusions: Cholesterol esters, triglycerides, carnitines and amino acids may constitute metabolites that are associated with insulinemic dietary patterns. Funding Sources: R00CA207736, NHLBI HHSN268201300008C.